Shape of Social Forestry in Rural India in the 21st Century - Shah, S. A. (Indian Forester, 1989)
Multiple use of land and use of multi-purpose indigenous trees with a proven merit for improving fertility status of soil would govern Social Forestry practices in the 21st century. It requires strong support of new research dim~nsions with well trained persons. The active role of Government and voluntary organisations is necessary for proper implementation of Social Forestry programme. Social Forestry of the 21st century will be a self-propelling, selfsustaining and largely a self-reliance movement of the people. Govt. would provide the required finance, Technology and market facilities.